The resilience of pollination interactions: importance of temporal phases. (19th January 2018) - Fantinato, Edy; Del Vecchio, Silvia; Gaetan, Carlo; Buffa, Gabriella
Abstract: Aims: The loss of species that engage in close ecological interactions, such as pollination, has been shown to lead to secondary extinctions, ultimately threatening the overall ecosystem stability and functioning. Pollination studies are currently flourishing at all possible levels of interaction organization (i.e., species, guild, group and network), and different methodological protocols aimed to define the resilience of pollination interactions have been proposed. However, the temporal dimension of the resilience of pollination interactions has been often overlooked. In the light of these considerations, we addressed the following questions: does a temporal approach help to reveal critical moments during the flowering season, when pollination interactions are less resilient to perturbations? Do pollination interactions evaluated at species, guild, group and network level show different patterns when assessed through time? Methods: We monitored contacts between plant and pollinator species in dry grassland communities every 15 days during the overall community flowering season (12 surveys). For each survey, we built a quantitative plant–pollinator interaction matrix and we calculated two sets of metrics characterizing, respectively, the diversity and the distribution of interactions across hierarchical levels. To describe the diversity of interactions, we calculated partner diversity (PD) at the species level, vulnerability/generality (V/G) at the guild level, and interaction diversity and evenness at the network level. The distribution of interactions was characterized by calculating selectiveness at the species and the network level, and modularity at the group level. We assessed the temporal variation of PD, V/G at the level of plants and pollinators, and species selectiveness, by means of Linear Mixed Models (LMMs). To investigate the temporal variation of indexes calculated at group and network level, we applied simple linear and quadratic regressions after checking for temporal autocorrelation in residuals. Important Findings: When taking into account the temporal dimension of interactions, the diversity of interactions showed different patterns at different levels of organization. At the species level, no relationship was disclosed between PD and time, when assessing the temporal trend of V/G separately for the guild of plants and pollinators we observed an asymmetric structure of interactions. Pollination interactions showed to be asymmetric throughout the flowering season; however, evenness of interactions and network selectiveness showed significant positive relationships with time, revealing a poorer network of interactions during the end of the flowering season. The temporal analysis of pollination interactions revealed a stronger risk of secondary extinctions at the end of the flowering season, due to a lower degree of redundancy and thus of resilience of the overall network of interactions.